Resisting Material Binaries: Unpacking persisting dichotomies of building materials in Central Africa - Robby Fivez (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The current discourse on African architecture is strongly influenced by social design—a practice for which architecture holds an important role in addressing complex societal questions and problems. The use of “alternative” building materials, as opposed to industrial materials like concrete or steel, is very central within this discourse. However, as this article argues, this strong binary approach to building materials is heavily influenced by colonial and postcolonial logic. To understand this continuity, I will trace some path dependencies visible in the Central African region from the colonial period to the present. In the first section, the material preferences of a Belgian architecture firm working in Rwanda in 2012 are related to the binaries of the architecture firms operating in this region in the 1970s and 1980s. In the second section, I discuss how the strong distinction between so-called “local” and “modern” materials is a remnant of the colonial period. Through an in-depth analysis of the shifting valuations of cement and burnt lime in Central Africa, the article aims to make these colonial categories feel less natural. Building on post-colonial science and technology studies (STS) scholarship, the conclusion proposes an alternative to binary thinking—a conscious material choice that tries to understand building materials as situated processes, allowing to go beyond the industry-driven denominators by which we currently value our building materials.